2016
DOI: 10.1177/1521025115622785
|View full text |Cite
|
Sign up to set email alerts
|

Is It a Different World? Providing a Holistic Understanding of the Experiences and Perceptions of Non-Black Students at Historically Black Colleges and Universities

Abstract: This qualitative study contributes an original holistic understanding of the perceptions and experiences of non-Black students (e.g., Asian American, Latino, and White) as they matriculate into historically Black colleges and universities (HBCUs), persist to graduation, and reflect on their experiences as graduates at HBCUs. Findings from this study confirm, challenge, and extend existing research regarding the preenrollment experience, institutional experience, and culminating outcomes of non-Black students e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Some evidence supports the idea that attending an HBCU may improve evaluations of blackness. Arroyo, Palmer, and Maramba (2016) found that attending an HBCU increased many Asian, Latino, and white students’ appreciation of diversity and decreased their prejudice. Relatedly, some studies suggest a relationship between attending predominantly black schools and increased self-esteem among black students (e.g., Oates 2004).…”
Section: Contact Theory and Students’ Evaluations Of Blacknessmentioning
confidence: 96%
“…Some evidence supports the idea that attending an HBCU may improve evaluations of blackness. Arroyo, Palmer, and Maramba (2016) found that attending an HBCU increased many Asian, Latino, and white students’ appreciation of diversity and decreased their prejudice. Relatedly, some studies suggest a relationship between attending predominantly black schools and increased self-esteem among black students (e.g., Oates 2004).…”
Section: Contact Theory and Students’ Evaluations Of Blacknessmentioning
confidence: 96%
“…A growing body of research explores the experiences of white, Latinx, and Asian HBCU students. These students may develop a heightened sense of racial otherness (Peterson and Hamrick 2009), increased appreciation for diversity, increased understanding of racism, and diminishing racial prejudice (Arroyo, Palmer, and Maramba 2016).…”
Section: How Hbcus Shape Racial Identitymentioning
confidence: 99%
“…For example, Arroyo and Gasman's () synthesis of the HBCU‐based literature for Black college student success offers a representative picture of the large number of these studies. Research on White and other non‐Black HBCU students occupies a smaller place in the literature (see, e.g., Arroyo et al., ; Brown, ; Carter & Fountaine, ; Closson & Henry, , ; Conrad et al., ; Dwyer, ; Gendrin & Chandler, ; Hall & Closson, ; Nixon & Henry, ; Palmer, Arroyo, & Maramba, ; Palmer & Maramba, in press‐a, in press‐b; Peterson & Hamrick, ; Strayhorn, ). However, to our knowledge, no existing study on White HBCU students has contextualized its findings within the complicated White enrollment picture presented in this chapter.…”
Section: Implications Of White Enrollment Trendsmentioning
confidence: 99%
“…None have utilized 2‐year institutions. However, despite this consistent 4‐year focus, each of these studies contextualizes itself within White population trends using one or more of the following data sources: (a) aggregate 2‐year and 4‐year figures (see, e.g., Arroyo et al., ; Hall & Closson, ; Peterson & Hamrick, ); (b) outdated figures that predate declines in White enrollment (see, e.g., Brown, ; Dwyer, ); or (c) examples of White growth that refer to sensationalized popular press stories and/or outliers such as Bluefield State College in West Virginia (see, e.g., Carter & Fountaine, ). Some studies leave out White population trends completely (see, e.g., Closson & Henry, , ; Strayhorn, ).…”
Section: Implications Of White Enrollment Trendsmentioning
confidence: 99%
See 1 more Smart Citation